Temporary migration entails benefits, but also costs, for sending and receiving countries - Joseph-Simon Görlach; Katarina Kuske (IZA World of Labor, 2022)
Many migrants do not stay in their host countries permanently. On average, 15% of migrants leave their host country in a given year, many of whom will return to their home countries. Temporary migration benefits sending countries through remittances, investment, and skills accumulation. Receiving countries benefit via increases in their prime-working age populations while facing fewer social security obligations. These fiscal benefits must be balanced against lower incentives to integrate and invest in host country specific skills for temporary migrants.
Keywords: F22; J61; O15; 330; temporary migration; integration; fiscal impact; remittances; entrepreneurship; brain circulation